Como entender a noção de espaço em Kant?: uma análise do período de 1756 a 1787 - Oliveira, Danilo Fernando Miner de (2013)
This dissertation shows that the notion of space in Kant is developed in close connection with the controversy over the nature of space conducted around the conceptions endorsed by Newton and Leibniz. It discusses the nature of space 1) as dependent on the relations of external objects, where its configuration as an apparition arises from the sensibility and 2) as not only independent of these objects, but also as the condition of their possibility, and by those means as absolute, universal and independent of all matter. It also shows the oscillating trajectory of the so-called 'pre-critic' writings between these two notions. Kant sometimes seems to advocate the Leibniz's thesis on the space, especially because it nourish the ideal conception of the nature of space, but also because it avoids some difficulties that are characteristic of Newton's, as those associated with the existence of void and with the methodological necessity of postulate the absolute character of space. At other times, however, we can observe a greater identification with the Newtonian thesis of the absolute space due to the increasing admiration and awe that Kant nurtured by the sciences of his day. Indeed, even if the absolute character of the space seems first to exceed the limits of human knowledge, its possibility is later demonstrated by the publication of the Critique of Pure Reason. Thenceforth, the independence from external objects that the notion of Newtonian space posits is a hallmark of Kant's critical thinking. It was only after the publication of the Inaugural Dissertation of 1770 that Kant expressed his most original thoughts on the space: the groundwork of space as a priori intuition. I argue that this innovation in Kant's thought does not constitute a definitive overcoming of the previous notions. Rather, it characterizes the critical articulation of the notion of space that allows not only to avoid the difficulties in which their contemporaries have fallen, but also exhibits the foundations of physics and mathematics as pure sciences. Finally, the arguments showed in the Inaugural Dissertation were incorporated systematically in the Critique of Pure Reason and better articulated in two exhibitions that support the notion of space: besides a pure intuition, the space must be also the subjective form of all external intuition. Only after these formulations it is possible to understand 1) the distinction employed by Kant between phenomena and noumena; 2) the split between philosophy and science; and 3) the foundation of so-called transcendental idealism.